2008
DOI: 10.1089/jwh.2007.0377
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Premenstrual Symptoms Impact Survey (PMSIS): A Disease-Specific Quality of Life Assessment Tool

Abstract: These results demonstrate that the PMSIS has excellent discriminative ability to detect differences in groups that are known to differ in terms of clinical criteria. The PMSIS can be used to educate consumers about the impact of their symptoms on QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…The prevalence of PMDD in this study was 5AE6%; this was comparable with recent findings (Adewuya et al 2008, Pearlstein et al 2008, Wallenstein et al 2008). The research methodology was an important factor influencing the results obtained, some researchers (Warner & Bancroft 1990, Landen & Eriksson 2003 have been cited by Adewuya et al (2008) for criticising the recommended DSM-IV daily prospective charting of symptom for two menstrual cycles as being 'extremely stringent and restrictive for mental disorder cases and almost impossible to achieve either in clinical or large scale study'.…”
Section: Rate Of Severe Pms/pmddsupporting
confidence: 92%
See 2 more Smart Citations
“…The prevalence of PMDD in this study was 5AE6%; this was comparable with recent findings (Adewuya et al 2008, Pearlstein et al 2008, Wallenstein et al 2008). The research methodology was an important factor influencing the results obtained, some researchers (Warner & Bancroft 1990, Landen & Eriksson 2003 have been cited by Adewuya et al (2008) for criticising the recommended DSM-IV daily prospective charting of symptom for two menstrual cycles as being 'extremely stringent and restrictive for mental disorder cases and almost impossible to achieve either in clinical or large scale study'.…”
Section: Rate Of Severe Pms/pmddsupporting
confidence: 92%
“…The prevalence of PMDD reported in studies conducted in the USA was from 3-8% (Gehlert & Hartlage 1997, ACOG 2000, Htay 2006, Casper 2007, Wallenstein et al 2008, Pearlstein & Steiner 2008. Rates published from other countries also vary greatly from 1AE2-50AE2% (Banerjee et al 2000, Mchichi Alami et al 2002, Wittchen et al 2002, Teng et al 2005, Takeda et al 2006, Rojnic Kuzman & Hotujac 2007, Adewuya et al 2008.…”
Section: Global Rates Of Pmddmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, studies have assessed HRQoL related to menopause and perimenopause, (Fuh et al 2003;Li et al 2000) the use of oral contraceptives, (Matsumoto et al 2007) and treatments for premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) (Freeman 2005;Pearlstein et al 2000). Wallenstein and colleagues developed a brief questionnaire, the Premenstrual Symptoms Impact Survey, as a web-based instrument for evaluating premenstrual symptoms and their impact on HRQoL (Wallenstein et al 2008). Those investigators found that the instrument was able to differentiate HRQoL among various groups, such as those at risk for PMS or PMDD.…”
Section: Discussionmentioning
confidence: 99%
“…Severe symptoms can lead to increased absenteeism, reduced productivity, and unpleasant mood changes, and can adversely affect social activities and quality of life. [8] This study was conducted via telephone interviews with experienced healthcare professionals in the area of women's health and with women experiencing premenstrual symptoms. negative perceptions that PMS is too private to discuss with a doctor or that PMS is something a woman should learn to live with), many women are either not aware of or not seeking treatment to relieve symptoms.…”
mentioning
confidence: 99%